2017
DOI: 10.1128/aac.02342-16
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutations in the Unfoldase ClpC1 of the Caseinolytic Protease Complex Are Associated with Pyrazinamide Resistance in Mycobacterium tuberculosis

Abstract: Previously, we showed that mutations in Mycobacterium tuberculosis panD, involved in coenzyme A biosynthesis, cause resistance against pyrazinoic acid, the bioactive component of the prodrug pyrazinamide. To identify additional resistance mechanisms, we isolated mutants resistant against pyrazinoic acid and subjected panD wild-type strains to whole-genome sequencing. Eight of the nine resistant strains harbored missense mutations in the unfoldase ClpC1 associated with the caseinolytic protease complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 34 publications
1
64
2
Order By: Relevance
“…9,10 On the basis of our observation that POA resistance-conferring clpC1 mutations are attenuated in vivo, whereas panD mutations did not cause a growth defect in vivo, we hypothesized that panD mutations—if they do occur in vivo—may be found frequently in vivo. Targeted PCR sequencing of panD revealed that 23 (82%) of the 28 POA-resistant strains isolated after POA treatment of mice contained panD mutations observed in multiple selection experiments in vitro 9,11,12 (Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 On the basis of our observation that POA resistance-conferring clpC1 mutations are attenuated in vivo, whereas panD mutations did not cause a growth defect in vivo, we hypothesized that panD mutations—if they do occur in vivo—may be found frequently in vivo. Targeted PCR sequencing of panD revealed that 23 (82%) of the 28 POA-resistant strains isolated after POA treatment of mice contained panD mutations observed in multiple selection experiments in vitro 9,11,12 (Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…10 M. tuberculosis ClpC1 works together with the ClpP1 and ClpP2 proteins of the caseinolytic protease complex and displays unfoldase and ATPase activities. 35,36 The Clp protease complex is crucial for viability of M. tuberculosis both in vitro and in vivo, 37,38 whereas the clpC1 gene on its own has been demonstrated to be essential for growth in vitro 31 and within macrophages.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…confirms the earlier finding that PanD is indeed a target of PZA . In addition, recent studies also identified another possible target of PZA as ClpC1, part of a protease complex involved in protein degradation, which is presumably important for persister survival. Furthermore, a recent study identified novel mutations in LprG (rv1411c), rv0521, rv3630, rv0010c, ppsC and cyp128 associated with POA/PZA resistance in MTB , which sheds new light on mode of action and resistance of this intriguing persister drug.…”
Section: Mechanisms Of Drug Resistance In Mtbmentioning
confidence: 98%
“…Mutations in pncA leading to the loss of PZase activity are the major mechanism of PZA resistance (4,10,11). PZA is known to interfere with multiple functions in Mycobacterium tuberculosis, including cytoplasmic acidification (12), disruption of membrane energy and transport function (12,13), inhibition of the protein degradation pathway via RpsA involved in trans-translation (14) and also ClpC1 protease (15,16), and energy production via PanD (17)(18)(19). Although resistance to PZA is mostly caused by pncA mutations and less commonly by rpsA, panD, and clpC1, clinical strains without these mutations such as 9739 (20) are known to exist.…”
mentioning
confidence: 99%